Preventive Effect of Garlic Juice on Renal Reperfusion Injury (Iranian Journal of Kidney Diseases, 2011)
Introduction. Renal reperfusion injury is associated with increased mortality and morbidity due to acute kidney failure. Oxidative stress induced with renal reperfusion affects glomeruli and tubular epithelium through reactive oxygen species; therefore, the use of medicinal plants appears rational for improvement of reperfusion effects. The aim of present study was to examine the preventive effect of garlic juice (Allium sativum) on renal reperfusion injury in rats.Materials and Methods. A total of 30 male Wistar rats were divided into 5 groups: control, garlic, sham (right nephrectomy), reperfusion, and reperfusion + garlic groups. After right nephrectomy, renal ischemia and reperfusion were induced. At the end of the experiment, all rats were killed and kidney function tests and histopathological examination were performed.Results. Reperfusion increased serum urea and fractional excretion of sodium levels, while it decreased urine potassium levels and creatinine clearance. However, garlic juice significantly decreased serum urea levels in the reperfusion + garlic group compared with the reperfusion group (P < .001). Preteatment with garlic juice also resulted in significant increase in urine potassium (P = .03) compared to reperfusion. Fractional excretion of sodium and creatinine clearance were also improved. On histological examination, rats pretreated with garlic juice had nearly normal morphology.Conclusions. The results of this study showed that garlic juice significantly prevented renal reperfusion-induced functional and histological injuries.